2017
DOI: 10.1177/1533317517703479
|View full text |Cite
|
Sign up to set email alerts
|

Examining Factors Affecting Caregiver Burden: A Comparison of Frontotemporal Dementia and Alzheimer’s Disease

Abstract: This study was conducted to compare the caregiver burden with regard to Alzheimer's disease (AD) and frontotemporal dementia (FTD) and to determine the factors affecting the caregiver burden of patients with AD and FTD. A comparative descriptive study design was used. The sample consisted of 90 patients with AD and 44 patients with FTD and their caregivers. Sociodemographic questionnaire, Mini-Mental State Examination (MMSE), the Caregiver Burden Inventory (CBI), Neuropsychiatric Inventory (NPI), and Functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Another most common behavioural problem of demented person is apathy, that is lack of interest in doing their usual activities. A study informed that most frequently observed symptoms for dementia is apathy (Küçükgüçlü et al 2017). Current study corroborates with the previous study in that it also showed care recipients experienced symptoms like apathy most.…”
Section: Discussionsupporting
confidence: 90%
“…Another most common behavioural problem of demented person is apathy, that is lack of interest in doing their usual activities. A study informed that most frequently observed symptoms for dementia is apathy (Küçükgüçlü et al 2017). Current study corroborates with the previous study in that it also showed care recipients experienced symptoms like apathy most.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, medical conditions that require the greatest caregiving time may not exert the greatest levels of burden to caregivers. One way to explain this nding is that though some medical conditions may require a less alarming amount of caregiving time, the intensity and emotion strain of caregiving involved in taking care of the patients may be equally, if not more, burdensome [18,28,31,32,[62][63][64]. While this nding helps shed light on the relationship between caregiving time and caregiver burden, it also emphasizes the need for more research to further chart factors that in uence caregiving time and caregiver burden (e.g., disease severity [65]).…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study, researchers found no signi cant difference in levels of burden reported by leukemia caregivers and cerebral palsy caregivers [24]. Comparing the impact of Alzheimer's disease and frontotemporal dementia on caregiver burden, study also indicates that there are no signi cant differences in levels of burden experienced in these two groups of caregivers [31]. Though evidence is needed to clarify mixed ndings in the literature, research is scarce.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings corroborate previous studies that find that caregiver burden may be correlated with time of care and greater dependence on ADL (Cruz e Hamdan, 2008;Yu et al, 2015;Cesário et al, 2017). Küçükgüçlü et al (2017) concluded that the factor that most affects the caregiver's burden is the decline in the performance of the ADL and neuropsychological symptoms, which primarily affect the time-dependent burden domain.…”
Section: Anexos_____________________________________________________112mentioning
confidence: 99%